IMPLEMENTASI SISTEM SURVEILANS KESEHATAN DI PUSKESMAS - Dinda Rizky Fadillah; Fanya Aullrelya Putry; Fidelma Felicia Br Sitepu; Nazwa; Rezky Khabiza Syahdu; Rizky Aditya Hutomo (MERDEKA : Jurnal Ilmiah Multidisiplin, 2026)
Health surveillance is an essential activity within the healthcare service system to monitor disease occurrences and to serve as a basis for health program decision-making. This study aims to describe the implementation of health surveillance at a community health center (puskesmas) using an interview-based approach. The research employed a descriptive qualitative method, with data collected through in-depth interviews with surveillance officers. The findings indicate that health surveillance activities have been conducted routinely and are integrated with the Ministry of Health information system; however, several challenges remain, particularly related to limited human resources and delays in reporting from service networks. Surveillance data are utilized as a basis for the formulation of disease control programs, thereby playing an important role in health intervention planning. The study concludes that the surveillance system has been implemented fairly well, but further strengthening is needed in terms of human resources and coordination with service networks.